Human responsibility towards environment in the Quran - Wahyudi, Deni (Indonesian Journal of Islam and Muslim Societies, 2012)
The research aims to describe the view of Islam about human relation with theenvironment according to the verses related to the duties and functions of thehuman being. This is interesting issue in the middle of allegations that the religionand the human perspective is one of the roots of the ecological crises thathappen in the world. By doing research on verses on the concept of humanbeing, concept of the environment and interaction between human theenvirontment, wil be drawn islamic teachings on relationship between humanbeing and the environment. The research will figure out comprehensive islamicconcept on the functions and duties of human being toward environment. Islambelieves that man and nature are interdependent and has an obligation to maintainthe balance of nature as manifestation of the faith and at the same time ashis mission as âabdulla>h and successor of god (khali>fatulla>h) the earth.Kajian dalam artikel ini bertujuan untuk menguraikan pandangan Islam mengenaiinteraksi manusia dengan lingkungan hidup menurut ayat-ayat terkait tugas danfungsi manusia. Isu ini menarik di tengah tuduhan bahwa agama dan cara pandangmanusia merupakan salah satu akar dari berbagai krisis ekologis yang dihadapioleh dunia. Dengan melakukan kajian terhadap ayat-ayat fungsi dan tugas manusia,pengertian lingkungan hidup dan interaksi antara manusia dan lingkuangannyaakan tergambar ajaran islam tentang hubungan antara manusia denganÂ lingkungan hidup. Dengan menguraikan ayat-ayat yang membahas fungsi dantugas manusia serta ayat yang terkait lingkungan hidup akan tergambar bahwaIslam memiliki pandangan yang komprehensif mengenai hubungan mansuia danlingkungan hidup dan tugas-tugasnya. Islam memandang bahwa manusia danalam merupakan satu kesatuan dan saling tergantung serta memiliki kewajibanuntuk menjaga keseimbangan sebagai manifestasi dari keimanan seorang hambasebagai âabdulla>h dan khalifah di muka bumi.